PENGARUH MOTIVASI, GAYA KEPEMIMPINAN TRANSFOMASIONAL DAN BUDAYA ORGANISASI MELALUI PEMENUHAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN CV. SINAR JAYA TEGAL - Vidi Sandi; Mr. Maufur (Multiplier: Jurnal Magister Manajemen, 2017)
The purpose of this research is (1) to know how much influence of motivation to job satisfaction, (2) to know how big influence of transformational leadership style to job satisfaction (3) to know how big influence of organizational culture to job satisfaction, (4) (5) to find out how big influence of leadership style of trasnformasional to employee performance, (6) to know how big influence of organizational culture to employee performance, (7) to know how big influence collectively between variable On employee performance with through job satisfaction variable. Respondents in this study as many as 115 people, the respondents are employees CV. Sinar Jaya Tegal. This research uses Structural Equation Modeling (SEM) which is run through AMOS program as its analysis tool. The result of data analysis proved that motivation influence to job satisfaction by 32% while for the transformational leadership style to job satisfaction get 6% and for organizational culture have no effect to job satisfaction is proved with minus value equal to (-14%). And for the relationship of motivation to employee performance have significant influence with 34%, transformational leadership style to employee performance have significant influence with value 17%, and for organizational culture to employee performance have significant influence with 4% and to influence collectively between motivation, Transformational leadership style and organizational culture to employee performance where through job satisfaction fulfillment got influence 39%, and the rest influenced by other factors which not in carefully in this research. Â Keywords:Â  Motivation, Transformational Leadership, Organizational Culture, Job Satisfaction, Employee Performance